TINJAUAN YURIDIS EKSEKUSI PUTUSAN ARBITRASE PADA PENGADILAN NEGERI BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 1999 TENTANG ARBITRASE DAN ALTERNATIF PENYELESAIAN SENGKETA - Bintang agustinus SImanjuntak (to-ra, 2021)
Article 60 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution stipulates that: "The arbitration award is final and has permanent legal force and is binding on the parties" In this Law there is a legal problem when the result of the decision of the Indonesian National Arbitration Board which is a final and binding decision if it is not implemented by the parties voluntarily, then one of the disputing parties can submit an application for its execution to the district court as provided for in Article 61 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. It is known that in principle the arbitration decision is final and binding. However, by stating that the arbitration award cannot be implemented, it certainly becomes a legal issue regarding the follow-up of dispute resolution between the parties, while in the arbitration law itself it does not a tour of the consequences of the inability to enforce the Arbitration decision. Keywords: execution, arbitration decision and district court